0392 Patient Perspective on Idiopathic Hypersomnia: Impact on Quality of Life and Satisfaction With the Diagnostic Process and Management. (25th May 2022) - Whalen, Marisa; Roy, Bailey; Steininger, Teresa; Dronamraju, Nalina; Enson, Daniel
Abstract: Introduction: Idiopathic hypersomnia is a debilitating central disorder of hypersomnolence characterized by excessive daytime sleepiness (EDS), severe sleep inertia, and prolonged nighttime sleep. The impact of idiopathic hypersomnia on quality of life (QoL) and patient satisfaction with the diagnostic process and management have not been well established. Methods: US patients with idiopathic hypersomnia completed an online survey (June 10 to July 2, 2021) assessing symptoms, impact, diagnosis, and management. Results: Respondents (N=290) were mostly female (88%), White (88%), and 25–44 years of age (mean, 38 years), had postsecondary education (88%), and were employed at least part time (63%). Self-reported years to idiopathic hypersomnia diagnosis were 0–1 (31%), 1–2 (16%), 2–5 (21%), 5–10 (13%), and 10+ (19%). Overall, 67% reported unreasonable delays to diagnosis (strongly/somewhat agree); 61% reported being misdiagnosed prior to their idiopathic hypersomnia diagnosis. Diagnoses of depression/anxiety, sleep apnea, or narcolepsy type 2 were reported by 72%, 25%, and 10% of respondents, respectively; these diagnoses were later removed and changed to idiopathic hypersomnia in 26%, 30%, and 57%, respectively. Symptoms of IH endorsed (strongly/somewhat agree) by ≥95% of patients were EDS (99%), reduced mental energy level and motivation to carry out daily activities (99%), and feeling as if they could never get enough sleep (98%). The following statements were endorsed by ≥90% of patients: idiopathic hypersomnia has had a significant negative effect on my QoL (79% strongly agree, 19% somewhat agree), has prevented me from being who I want to be (66% strongly agree, 26% somewhat agree), and is often unrecognized and under-diagnosed (67% strongly agree, 24% somewhat agree), and the idiopathic hypersomnia community is underserved (67% strongly agree, 24% somewhat agree). Specific QoL impacts (strongly agree) included constantly struggled with maintaining relationships (65%), had suicidal thoughts (34%), and chose not to have children (25%). Nearly half (49%) of patients reported dissatisfaction with the management of their idiopathic hypersomnia (not very/not at all satisfied). Conclusion: The survey findings indicate that patients with idiopathic hypersomnia experience a profound negative impact on QoL and dissatisfaction with their diagnostic journey and management. Support (If Any): Jazz Pharmaceuticals, with participation of the Hypersomnia Foundation.